2015
DOI: 10.1016/j.drugalcdep.2015.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Solitary cannabis use in adolescence as a correlate and predictor of cannabis problems

Abstract: Background Most adolescent cannabis use occurs in social settings among peers. Solitary cannabis use during adolescence may represent an informative divergence from normative behavior with important implications for understanding risk for cannabis problems. This longitudinal study examined associations of adolescent solitary cannabis use with levels of cannabis use and problems in adolescence and in young adulthood. Methods Cannabis using-adolescents aged 12–18 were recruited from clinical programs (n=354; 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 28 publications
3
33
2
Order By: Relevance
“…Creswell et al . found that solitary users of marijuana were more likely to be male (61.2% of solitary users) , whereas Tucker et al . showed that they were less likely to be male (38.0% of solitary users) .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Creswell et al . found that solitary users of marijuana were more likely to be male (61.2% of solitary users) , whereas Tucker et al . showed that they were less likely to be male (38.0% of solitary users) .…”
Section: Resultsmentioning
confidence: 93%
“…However, in a predominantly clinical sample, Creswell et al . indicated that 64.7% of participants who were marijuana users reported solitary cannabis use at least once in adolescence (aged 12–18 years) .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, solitary cannabis use during adolescence has been shown to be a significant risk factor for lower physical health and increased substance-related problems in young adulthood (42). Creswell and colleagues (43) demonstrated a concurrent relationship between solitary cannabis use, more frequent cannabis use, and CUD symptoms during adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Also, results based on data from the 2005–2011 National Surveys on Drug Use and Health (N=394,400) showed that the prevalence of CUD is different among Blacks (2.5%) as compared to Hispanics (1.8%) (18). Solitary cannabis use (a percentage of total use episodes) in adolescence predicted CUD symptoms at age 25 after controlling for demographic variables and the frequency of adolescent cannabis use (19). Lastly, CUD is associated with lower educational attainment (20, 21).…”
Section: Introductionmentioning
confidence: 99%